The Financial Flows of the Transnational Crime: Some Preliminary Empirical Results - Friedrich Schneider (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Until 2008, the growth of the world economy was quite strong and improved the economic well-being all over the globe, but this development was also accompanied by some risks. One of them is transnational crime, which has shown a remarkable increase in the last 20 years3. This raises the following two questions: (1) How is transnational crime financed, and what do we know about this financing? (2) What economic implications does transnational crime have? In this contribution question (2) will be very briefly answered, however the main focus lies on providing a more detailed answer on the financing of transnational crime (question 1). Additionally a detailed analysis of the finances of transnational crime is crucial to reduce their financial options, so that the basis of their operations is at least limited. Such an analysis is another goal of this chapter. My paper is structured as follows: section 2 provides a literature review on the kinds of transnational crime financing. Section 3 shows the infiltration of transnational crime into the economic system. In section 4 some conclusions and policy recommendations are drawn.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330